The Effect of Multiple-Slot Substitution Drill on Students’ Grammar Mastery at the Eighth Grade Students of SMP Islam Al Akbar Malang - Muslimah; Yasminto, Muhammad (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2022)
This study aims to investigate the effect of multiple-slot substitution drill on students’ grammar mastery through true experimental research design conducted with an experimental group and a control group. Target population of this study was all the eighth grade students of SMP Islam AL Akbar, Singosari- Malang 2021/2022. The researcher took 46 students as sample of the study, by using saturated sampling, 23 students as experimental group and 23 students as control group. To collect data, she used grammar written post-test with 20 items in multiple-choice format. In analyzing data, she used IBM SPSS statistic versions. 20 application of independent t.test to know the differences between experimental and control groups. After collecting and calculating data, tshe found that mean score and standard deviation of experimental group were 77.39 and 5.41, while mean score of control group was 70.22 and standard deviation was 13.1. In testing hypothesis, she used t-test formula. She found that F value =13.636, Sig (2-tailed)= 0.019 < 0.05, at the level significance of df = 44. So, null hypothesis was rejected and the alternative hypothesis could be accepted. It means that students taught using multiple-slot substitution drill achieve better than students taught without using multiple-slot substitution drill.